2016
DOI: 10.15171/hpp.2016.04
|View full text |Cite
|
Sign up to set email alerts
|

Health promoting hospitals: a study on educational hospitals of Isfahan, Iran

Abstract: Background: The current situation of health promotion (HP) services in hospitals of Iran is unclear. The aim of this study was to assess the status of HP in hospitals in Isfahan, Iran. Methods: This study is a cross-sectional survey in which 9 educational hospitals selected through census sampling. HP self-assessment was used for the data collection. The assessment teams formed, and evidence examined in line with the tools. Results: The results identified five categories of HP activities in the hospitals con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
3
14
0
2
Order By: Relevance
“…In the present study, the health promotion standards in governmental and non-governmental hospitals of East-Azerbaijan was studied. According to the results of this study, the total HPH score of East-Azerbaijan hospitals was 56.06±21.27 that is higher than those of educational hospitals in Isfahan (48.80±9.80) (8) and also 38 hospitals from four provinces of Iran (54.1±15.1) (12). These finding indicated that although hospitals in East-Azerbaijan had better compliance with HPH program compared with those of other provinces of Iran, they had a long distance to accomplish the objectives of HPH standards.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In the present study, the health promotion standards in governmental and non-governmental hospitals of East-Azerbaijan was studied. According to the results of this study, the total HPH score of East-Azerbaijan hospitals was 56.06±21.27 that is higher than those of educational hospitals in Isfahan (48.80±9.80) (8) and also 38 hospitals from four provinces of Iran (54.1±15.1) (12). These finding indicated that although hospitals in East-Azerbaijan had better compliance with HPH program compared with those of other provinces of Iran, they had a long distance to accomplish the objectives of HPH standards.…”
Section: Discussionmentioning
confidence: 62%
“…This concept is new in Iran, and there is not much research to evaluate its effectiveness in Iranian hospitals. In a study in Isfahan, assessment of nine educational hospitals showed that based on health promotion score, only one hospital was at the good level (8). In another study in the northwest of Iran, form the administrative and clinical staff point of view, the "management policy" had the lowest score and "patient information and intervention" had the highest score in Tabriz heart hospital.…”
Section: Introductionmentioning
confidence: 98%
“…The incidence of COVID-19 in these cities in the four-months was about 246 per 100,000 people (Table 3). It seems this migration was due to the proximity of these counties to Isfahan (average distance of 32 km), more facilities in Isfahan (27), and the low capacity of hospitals in these cities (about 126 hospital-beds). Another reason for importing cases was the reduction of travel restrictions since April 15.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of COVID-19 in these cities in the four-months was about 246 per 100,000 people (Table3). It seems this migration was due to the proximity of these counties to Isfahan (average distance of 32 km), more facilities in Isfahan (27), and the low capacity of hospitals in these cities (about 126 hospital-beds). Another reason for importing cases was the reduction of travel restrictions since April 15.…”
Section: Please Insertmentioning
confidence: 99%